In situ diagnostic assessment for the infiltration rate of the northern Gaza wastewater infiltration basins - Abualtayef, Mazen; Abushbak, Thaer; Abu Alnoor, Ahmed; Al-Najjar, Hassan (International Journal of Engineering and Technology, 2020)
The Northern Gaza Emergency Sewage Treatment (NGEST) is addressed as a promising water management intervention strategy to maintain the sustainability of groundwater aquifer in the Gaza Strip. This study assesses the current operational status of the north-ern Gaza wastewater infiltration basins located at NGEST project. In situ diagnostic assessment was performed at two spots (A) and (B) located inside the basin (3). The results of sieve analysis and bulk density indicate that the soil at the spot (B) is finer than of spot (A) where the contents of the fine material and bulk densities were 13% and 1544 kg/m3 at the spot (A) and 23.7% and 1544 kg/m3 at the spot (B). In terms of the infiltration capacity, the nature of soil at the spot (A) exhibits better initial and saturated infil-tration rate in comparison to the soil at the spot (B), where the initial and saturated infiltration rates were 2.88 and 0.43 for spot (A) and 0.29 and 1.73 meters per day for spot (B), respectively. Thus, the diagnostic assessment for the northern Gaza wastewater infil-tration basins indicates that the soil classification is silty sand and the infiltration rates range between about 3 and 0.3 meters per day.Â Â